My dear governess : the letters of Edith Wharton to Anna Bahlmann - Wharton, Edith, 1862-1937 (Yale University Press, 2012)
"An exciting archive came to auction in 2009: the papers and personal effects of Anna Catherine Bahlmann (1849-1916), a governess and companion to several prominent American families. Among the collection were one hundred thirty-five letters from her most famous pupil, Edith Newbold Jones, later the great American novelist Edith Wharton. Remarkably, until now, just three letters from Wharton's childhood and early adulthood were thought to survive. Bahlmann, who would become Wharton's literary secretary and confidant, emerges in the letters as a seminal influence, closely guiding her precocious young student's readings, translations, and personal writing. Taken together, these letters, written over the course of forty-two years, provide a deeply affecting portrait of mutual loyalty and influence between two women from different social classes. This correspondence reveals Wharton's maturing sensibility and vocation, and includes details of her life that will challenge long-held assumptions about her formative years. Wharton scholar Irene Goldman-Price provides a rich introduction to My Dear Governess that restores Bahlmann to her central place in Wharton's life"--Provided by publisher